Metacognitive awareness components of high-academic ability students in biology hybrid learning: Profile and correlation - Iin Hindun; N. Nurwidodo; Azizul Ghofar Candra Wicaksono (University of Muhammadiyah Malang, 2020)
Metacognitive awareness has been considered as one of the factors within students that determines learning success. It can be developed through a hybrid learning approach. The purpose of this quantitative research was to examine the metacognitive awareness profile of students with high-academic ability in hybrid learning implementation. The subjects of this study were the students of XI-Science class of state senior high school of Malang. The Metacognitive Awareness Inventory was used as the data collection instrument, while descriptive statistics and Pearson Product-Moment were chosen as the data analysis techniques. The results of the study informed that the students’ metacognitive awareness was divided into four categories, i.e. very good (9%), good (43%), enough (46%), and very low (2%). The three components of metacognitive awareness were classified as